Elimination of gases in the supply channel to manufacture a 3” ball - Agreda Sanguinetti, Ángel Josué (2011)
This process begins when the ball production unit receives the liquid steel from the steelworks area in spoons, then the steel is emptied into the turntable where the solidification of the 3 ”ball clusters will occur, the turntable consists of 40 arms, 2 bunches of balls are obtained in each arm, making a total of 80 bunches of balls for one turn of the turntable. For what is considered to be a high production line, since it operates 24 hours a day. The inner state of a 3 ”ball is first evaluated to determine if the defect is caused by grinding, once this possibility was ruled out, 3 experimental tests were carried out in an artisanal way, which consisted of modifying the feeding system of the sand souls for 3 ”balls. In the first modification of the core, the feeding is from the bottom and from the side of the mold; in the second modification of the feeding system, the balls of the upper part were isolated; and in the third and last modification of the 3 ”ball feeding system, the balls continued to be isolated from the top, and a central feeding system was made with 2 inclined outlets for the two feeders. In each test performed, the dolls were visually inspected and the balls were inspected. In the ball area, the feeding system after solidifying is called "dolls". In addition, radiographic plates were taken to evaluate the final state of the balls, and to evaluate the behavior of the feeders.